Frequency of Gingivitis and its Associated Factors in 16–60-Year-Old Patients Reporting at the Dental Hospital: A Cross-Sectional Study - Farhan Javed, Ali Anwer, Nazia Kalim, Ahmed Mukhtar Chema, Kanza Nawadat, Sania Saqib, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gingivitis is one of the most prevalent noncommunicable diseases which affecting people in Pakistan. For the preservation of great overall health, dental health must be maintained. So, there is need to determine the prevalence, socioeconomic impact, and educational status of gingivitis with the associated factors amongst widespread age group. Objective: This research focused on the frequency of gingivitis and its associated factors between the age group of 16–60-year-old patients. Study Design: Cross sectional study Study Setting: This study was conducted at department of Dentistry Avicenna Medical & Dental College Hospital Lahore from April 2022 to September 2022. Methodology: In the present study, a non-probability/convenient sampling technique was used. The 115 patients who had a gingival index scoring from 1-3 were included in the study. Patients with no plaques were excluded from the study. The WHO oral health assessment with some modifications was included as a part of the questionnaire. During the preliminary screening of the subjects, the demographic characteristics including age, gender, BMI, marital, socio-economic, and educational status were noted. A mouth mirror and a pointed explorer technique were used to diagnose caries which helps to fulfil the data of gingival index, plaque index, decayed missing filled teeth index, oral hygiene index simplified. Continuous and categorical data were analyzed by using SPSS version 20. Results: Out of 115 participants, there were 55 (47.8%) males and 60 (52.17%) females enrolled in the study with an average age of 39.51 ± 9.72 years. In this study, the overall BMI of the participants was 39.0 ± 22.3 kg/m2. Study results showed that the DMFT and OHI-S were significantly different (p<0.05). The DMFT and OHI-S showed the highest value amongst the patients suffering from moderate gingivitis. Conclusion: This study concluded that gingivitis and its associated factors played a major role in poor oral health. Amongst the age group between 16 to 60 years old, the 30-40 years were more prevalent to gingivitis. The DMFT and OHI-S were significantly different in mild moderate, and severe gingivitis. This study also indicated that the married, low-income status and the graduated patient had achieved bad oral hygiene. The study revealed that the ages between 30 to 40 years were their prime time for social and economic burden on males and also this is the post menstrual age in female, and by this time their health was already severely impaired. This may be a contributing factor to the increased incidence of gingivitis. However, the GI, DMFT, and OHI-S must have an access to fluoride and sealant programs as soon as possible to reduce the prevalence of tooth decay. Keywords: Gingivitis, DMFT, OHI-S, Factors, Dental Hospital, periodontal disease, risk factors/indicators